Effects of the Implementation of a program based on the 5s methodology for the minimization of risks and accidents at work - Perez Bernardo, Marilyn Susan (2025)
The effects of the implementation of a program based on the 5S methodology for the minimization of risks and accidents at work in an Electrical Services company (Lima - Peru) were evaluated. The study is of an applied type and of a pre-experimental design, the analysis unit covered 19 operational and administrative units of the company in question during the years 2022 and 2023. The data collection was carried out by the observation method, using checklists, records of inspections and accidents that were validated by the criteria of judges. The comparative analysis was carried out after verifying the normality of the data, determining the use of the Student's t test. The results show significant differences due to the implementation of 5S. Regarding risks, there was a significant reduction, due to the intervention of the independent variable: 5S methodology, since the average risk of the post-test (6.00) is lower than that obtained in the pre-test (16.20), with a significance level of p<0.044. In relation to accidents, a notable reduction was also recorded, due to the intervention of the independent variable: 5S methodology, since the average number of accidents in the post-test (2.14) is lower than that obtained in the pre-test (4.00), with a significance level of p < 0.021.